The Meaning of Sarong in Madurese Culture: A Symbolic Analysis of Films on YouTube Mata Pena - Ni'mahtul Laily; Miftahur Roifah (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
The purpose of this research is to examine the symbolic meaning of the Madurese sarong as a cultural symbol in short films featured on the YouTube channel Mata Pena. The background of this research highlights the significance of the sarong as a symbol of identity and a representation of cultural values in Madurese society. The sarong is not only viewed as an item of clothing but also as a marker of social status, tradition, and honor passed down through generations. This research employs a qualitative method with a semiotic analysis approach based on Charles Sanders Peirce's theory, focusing on three main elements: sign, object, and interpretant. This framework is used to understand how the meaning of the sarong is constructed within cultural and social contexts. The findings reveal that the Madurese sarong carries profound meaning, both as a symbol of social status and cultural identity and as a representation of tradition, politeness, religion and honor in Madurese society. Keyword: Sarong, Semiotics, Cultural Identity, Madura, Short Film